PENERAPAN KEGIATAN â€œPAPER QUILLINGâ€ UNTUK KETERAMPILAN MOTORIK HALUS ANAK USIA 5-6 TAHUN - Dedek Wahyuningtyas; Isfauzi Hadi Nugroho; Anik Lestariningrum (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
Problems faced by children related to softmotoric skills especially when coordinating small muscles to perform daily activities is when drawing using stationery correctly there is still holding a pencil, cutting also not too skilled, expressing movement in detail while the child should be standard age 5 These achievements have been good for 6 years. Responding to this problem, it was found that the Paper Quilling activity that was designed by the teacher using simple raw materials owned around the child and then carried out with the concept of creative play turned out to interest the child to better process the increased skills. The purpose of this study will describe how the results of the development of softmotoric skills skills after using Paper Quilling activities especially in students aged 5-6 years. The research design used is descriptive qualitative with assessment techniques using observation and documentation where the observation instrument was developed referring to the STPPA of softmotoric skills aspects of children aged 5-6 years. The subjects were 13 children group B TK Pertiwi 2 Sidoarjo Kabupaten Nganjuk. The results of the data after being collected are analyzed using triaculation of data and then described in a natational manner by studying so that the softmotoric skills skills can be described. Based on the results of data analysis, it was found that the improvement of children's skills in softmotoric skillsic aspects could be improved by using Paper Quilling activities. From the results of this study it is recommended that Paper Quilling activities can be used by other institutions to further accomodate the application according to the stages of child development because it is proven effective.